Student advancement in tertiary learning environments: Shift from the obstacle course to the dancefloor - Dix, Steve (Elsevier, 2018)
This paper explores a path for those of us in the university classroom to re-think our approach to the millennial students we teach. The research question ponders what foremost initiatives we may implement to advance our students’ learning. A signposted series of ideas is posted and prompted by the first four letters in the alphabet. “A” is for “Activating our Millennial Learners.” This is call to set our students up for success at the start. “B” stands for “Building Bonds of Knowledge Retention” for core discipline knowledge. What long term learning should our students take forward? The third initiative is “Collaboration” and urges us to work more closely with those co-responsible for delivering the learning. The final initiative is “Data Analytics”. How can we prioritize our students to leverage analytical skills around big data? In conclusion, the challenge is to shift our focus away from being an ‘instructor’ to becoming a ‘partner in learning.’